Uniwersytet przyszłości organizacją fraktalną? - Leja, Krzysztof (University in the Future as the Fractal Organization?, 2006)
Due to the decrease of public spending and new challenges the universities are asked to develop their organization to be more effective. The author proposes to implement some ideas of fractal organization to a university organization to remove the vertical and horizontal boundaries and to become more flexible. Some characteristic of fractal organization such as self-similarity of entities, selforganization, navigation, vitality and dynamic adopted lo a contemporary university offer better opportunity for creativity development in the knowledge society. University fractal organization favours both knowledge diffusion (groupwork, interdisciplinary research and education) and better response lo the challenges.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 149-158